An Update on Hdv: Virology, Pathogenesis and Treatment. Issue 3 (April 2013) - Alvarado-Mora, Mónica V; Locarnini, Stephen; Rizzetto, Mario; Pinho, João R Rebello
Hepatitis delta is an inflammatory liver disease caused by infection with HDV. HDV is a single-stranded circular RNA pathogen with a diameter of 36 nm. HDV is classified in the genus Deltavirus and is still awaiting a final taxonomic classification up to the family level. HDV shares similarities with satellite RNA and viroids including a small circular single-stranded RNA with secondary structure that replicates through the 'double rolling circle' mechanism. The HDV RNA genome is capable of self-cleavage through a ribozyme and encodes only one structural protein, the hepatitis delta antigen (HDAg), from the antigenomic RNA. There are two forms of HDAg, a shorter (S; 22 kDa) and a longer (L; 24 kDa) form, the latter generated from an RNA editing mechanism. The S form is essential for viral genomic replication. The L form participates in the assembly and formation of HDV. For complete replication and transmission, HDV requires the hepatitis B surface antigen (HBsAg). Thus, HDV infection only occurs in HBsAg-positive individuals, either as acute coinfection in treatment-naive HBV-infected persons, or as superinfection in patients with pre-existing chronic hepatitis B (CHB). HDV is found throughout the world, but its prevalence, incidence, clinical features and epidemiological characteristics vary by geographic region. There are eight genotypes (1 to 8) distributed over different geographic areas: HDV-1 is distributed worldwide, whereas HDV-2 to 8 are seen more regionally. Levels of HDV viraemia change over the course of HDV infection, being significantly higher in patients with early chronic hepatitis than in cirrhosis. Chronic HDV infection leads to more severe liver disease than chronic HBV monoinfection with an accelerated course of fibrosis progression, an increased risk of hepatocellular carcinoma and early decompensation in the setting of established cirrhosis. Current treatments include pegylated interferon-α and liver transplantation; the latter of which can be curative. Further studies are needed to develop better treatment strategies for this challenging disease.